Extração e fracionamento de óleo essencial de piper hispidinervum e produção de nanoemulsão e nanocápsulas : experimentos e modelagem - Rossa, Guilherme Evaldt (2019)
The Piper hispidinervum is a shrub of the family Piperaceae found in great quantity in the valley of the river Acre. The essential oil of this plant demonstrate its amebicidal activity against Acanthamoeba polyphaga, nematicidal activity against Meloidogyne javanica and carrapaticidal activity against Rhipicephalus (Boophilus) microplus larvae. Despite these promising properties, high volatility, low solubility in water and susceptibility to degradation by physical and chemical agents can compromise the biological activity of essential oils, thus promoting the study of new forms of application, encapsulation and controlled release, and protection of its active constituents. The objective of this work is to perform the extraction and fractionation of the volatile extract of Piper hispidinervum and the production of nanoemulsion and nanocapsules with subsequent release study. The extraction step concluded that the effect of the change in operating pressure did not significantly change the yield of the process and the composition of the essential oil. The fractionation of the essential oil resulted in the obtaining of fractions with different compositions of the safrol and terpinolene. The nanoemulsions had good stability and the polycaprolactone nanocapsules obtained satisfactory results in terms of particle size and encapsulation efficiency. The evaporation profiles of the nanoemulsion and nanocapsules indicated that the change in the volatility of the essential oil promoted by the physical coating of the nanocapsules was very small and the proposed mathematical model presented a good representation of the experimental data.